The Self-Restrained Positive Legislator: Assessing the Constitutional Review of Legislative Omissions in Lithuania - Pūraitė-Andrikienė Dovilė; Valuta Andrius (Baltic Journal of Law & Politics)
The function of constitutional courts has undergone significant transformation in recent decades. More frequently, constitutional courts, instead of dealing with existing legislation, assume the role of assistants to the legislator. Some of these courts also control the absence of legislation or legislative omissions. This article seeks to explore the approach of the Lithuanian Constitutional Court in handling cases of legislative omission, particularly focusing on its efforts to strike a balance between respecting the autonomy of law-making institutions and upholding the supremacy of the Constitution. The text addresses the extent to which the Constitutional Court has adhered to the principle of self-restraint, ensuring that its interventions do not unduly encroach upon the prerogatives of law-making institutions. To reach this, the following tasks are undertaken and dealt with: 1) to shed light on the concept and typology of legislative omissions in comparative constitutional law, as well as the trends of their investigation (including statistical data) in European countries; 2) to analyse the official constitutional doctrine formulated by the Lithuanian Constitutional Court on the concept of legislative omissions and the scope of the Court’s power to examine legislative omissions; 3) to analyse the approach of the Lithuanian Constitutional Court to legislative omissions from a quantitative point of view, i.e. to examine the statistics of this Court in dealing with legislative omissions and the reasons for its changes.